Analisis Pengaruh Perbedaan Organisasi Internal dan Eksternal terhadap IPK Mahasiswa Pendidikan IPA Stambuk 2023 Universitas Negeri Medan: (Analysis of the Influence of Differences in Internal and External Organizations on the GPA of Science Education Students of the 2023 Stambuk Program, State University of Medan) - Tarigan , Tasya Natalia; Napitupulu , Irene Paulina; Silalahi, Romanna; Pakpahan , Rahel; Siregar , Uyun Hanip (BIODIK, 2025)
This study aims to analyze the influence of different types of student organizations—internal campus organizations, external campus organizations, and a combination of both on the Grade Point Average (GPA) of Science Education students enrolled in the 2023 batch of the State University of Medan. The background of the study stems from the findings of various studies showing that organizational activities can develop non-academic competencies such as time management, leadership, and learning motivation, which have the potential to influence student academic achievement. The study used a comparative descriptive quantitative approach with a saturated sampling technique, involving all students who were actively involved in organizations and were willing to complete a questionnaire. Data were collected through questionnaires and analyzed using descriptive statistics to observe trends in GPA differences in each organizational group. The results showed that students active in internal organizations had an average GPA of 3.636; students in external organizations 3.612; while students who participated in both types of organizations achieved the highest GPA, namely 3.729. These findings confirm that organizational activities do not hinder academic achievement, but instead provide a positive contribution if students are able to manage their time and responsibilities well. This study has implications for the development of student policies that encourage balanced and structured organizational involvement. Abstrak. Penelitian ini bertujuan untuk menganalisis pengaruh perbedaan jenis organisasi yang diikuti mahasiswa organisasi internal kampus, organisasi eksternal kampus, serta kombinasi keduanya terhadap Indeks Prestasi Kumulatif (IPK) mahasiswa Pendidikan IPA Stambuk 2023 Universitas Negeri Medan. Latar belakang penelitian berangkat dari temuan berbagai studi yang menunjukkan bahwa aktivitas berorganisasi dapat mengembangkan kompetensi non-akademik seperti manajemen waktu, kepemimpinan, dan motivasi belajar, yang berpotensi memengaruhi prestasi akademik mahasiswa. Penelitian menggunakan pendekatan kuantitatif deskriptif komparatif dengan teknik sampling jenuh, melibatkan seluruh mahasiswa yang aktif berorganisasi dan bersedia mengisi angket. Data dikumpulkan melalui kuesioner dan dianalisis menggunakan statistik deskriptif untuk melihat kecenderungan perbedaan IPK pada masing-masing kelompok organisasi. Hasil penelitian menunjukkan bahwa mahasiswa yang aktif pada organisasi internal memiliki rata-rata IPK 3,636; mahasiswa organisasi eksternal 3,612; sedangkan mahasiswa yang mengikuti kedua jenis organisasi memperoleh IPK tertinggi, yaitu 3,729. Temuan ini menegaskan bahwa aktivitas organisasi tidak menghambat prestasi akademik, bahkan memberikan kontribusi positif apabila mahasiswa mampu mengelola waktu dan tanggung jawabnya dengan baik. Penelitian ini memberikan implikasi bagi pengembangan kebijakan kemahasiswaan yang mendorong keterlibatan organisasi secara seimbang dan terstruktur.